1991
DOI: 10.1007/bf01320233
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermiogenesis in the gastropodHeliacus variegatus (Architectonicidae), with description of a banded periaxonemal helix

Abstract: Spermiogenesis and spermatozoa of the marine gastropod Heliacus variegatus Gmelin were examined using transmission electron microscopy (TEM). Mature spermatozoa are composed of an acrosomal vesicle, helical nucleus, elongate midpicce, annulus, glycogen piece and short end piece. The midpiece consists of a 9 + 2 axoneme, nine coarse fibres, and a banded helix, all enclosed by a continuous mitochondrial sheath (with multiple, helically coiled grooves). Anterior extensions of the mitochondrial sheath and banded h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Groups classically assigned to the Prosobranchia but now considered to be primitive heterobranchs such as the Valvatoidea, Pyramidelloidea and Architectonicoidea, have become the focus of detailed anatomical and phylogenetic investigations (Haszprunar 1988;Rath 1988;Ponder 1990aPonder , b , 1991. Significantly, the taxonomic implications of sperm and osphradial ultrastructural research on these groups have largely been in accord with results suggested by comparative anatomy (Thompson 1973;Haszprunar 1985a, b;Healy l982,1988aHealy l982, , b , 1990aHealy l982, , 1991Healy & Jamieson 1991). In this account I survey sperm ultrastructure and development within the basal Heterobranchia and relate these data to the classification and phylogeny of the families and superfamilies presently assigned there.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Groups classically assigned to the Prosobranchia but now considered to be primitive heterobranchs such as the Valvatoidea, Pyramidelloidea and Architectonicoidea, have become the focus of detailed anatomical and phylogenetic investigations (Haszprunar 1988;Rath 1988;Ponder 1990aPonder , b , 1991. Significantly, the taxonomic implications of sperm and osphradial ultrastructural research on these groups have largely been in accord with results suggested by comparative anatomy (Thompson 1973;Haszprunar 1985a, b;Healy l982,1988aHealy l982, , b , 1990aHealy l982, , 1991Healy & Jamieson 1991). In this account I survey sperm ultrastructure and development within the basal Heterobranchia and relate these data to the classification and phylogeny of the families and superfamilies presently assigned there.…”
Section: Introductionsupporting
confidence: 55%
“…The following summary and supporting micrographs ( Fig. 4A-L Medina et al 1985Medina et al ,1986Medina et al ,1988Healy l982,1988bHealy l982, ,1990aHealy l982, , 1991Healy & Jamieson 1991).…”
Section: Spermiogenic Featuresmentioning
confidence: 86%
See 1 more Smart Citation
“…Plesiomorphic spermatozoa are found in externally fertilizing gastropods, whereas modified spermatozoa are found in internally fertilizing gastropods such as neritimorphs, the vetigastropod genus Zalipais (Healy, 1990a) and Apogastropoda. The characters used here have been taken from the studies of Thompson (1973b), Healy (1983a, b, 1986a, b, c, 1987, 1988, 1990a, b, 1991, 1993), Healy & Willan (1984, 1991), Koike (1985), Healy & Jamieson, 1989, 1991) and Ponder & Lindberg (1997).…”
Section: Charactersmentioning
confidence: 99%